INFORMATION ASYMMETRY AND MARKET FAILURE (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is the main occupation of 80% of India's rural population. Information Asymmetry is one of the crucial factors which are one of the causes of market failure of agricultural production. This study shows that the most significant cause of price fluctuations in crop procurement and its information asymmetry is in the form of a substantial gap in awareness of MSP among farmers all over India. The MSP policy in India is indifferent regarding information and the price of crops. This is the actual problem from which every farmer in India suffers. The majority of farmers in India have information asymmetry regarding MSP, leading to problems with what to produce, when to produce, and how much to produce. That is why the crops' marketable surplus [production – consumption] is very low. Information asymmetries among the buyers or sellers create imperfections in the crop market so they do not get the actual benefit of the Minimum Support Price (MSP), leading to price fluctuations and market failure. Therefore, information failure is one of the major causes of market failure. The government sets minimum support based on ground level, so it is very important to aware farmers about it to make investments in their farms and encourage or inspire them to be friendly with the advanced machinery and technologies to shoot up their farm productivity, which also leads to an increase in a farmer’s net income.